Quantitative Cryo-Electron Tomography - Navarro, Paula P. (Frontiers in Molecular Biosciences, 2022)
The three-dimensional organization of biomolecules important in the function of all living systems can be determined by cryo-electron tomography imaging under native biological contexts. Cryo-electron tomography is continually expanding and evolving, and the development of new methods that use the latest technology for sample thinning is enabling the visualization of ever larger and more complex biological systems, allowing imaging across scales. Quantitative cryo-electron tomography possesses the capability of visualizing the impact of molecular and environmental perturbations in sub-cellular structure and function to understand fundamental biological processes. This review provides an overview of current hardware and software developments that allow quantitative cryo-ET studies, their limitations and how overcoming them may allow us to unleash the full power of cryo-ET.